Exploring the impacts of senescence on implantation and early embryonic development using totipotent cell-derived blastoids - Yuxin Luo; Chenrui An; Ke Zhong; Ping Zhou; Dan Li; Hui Liu; Qing Guo; Wei Wei; Hen Pan; Zheying Min; Rong Li; Yang Yu; et al. (Journal of Advanced Research)
Introduction: Advanced maternal age is associated with reduced implantation and pregnancy rates, yet the underlying mechanisms remain poorly understood, and research models are limited. Objectives: Here, we aim to elucidate the impacts of senescence on implantation ability by employing blastoids to construct a novel research model. Methods: We used a novel three-dimensional system with totipotent blastomere-like cells (TBLCs) to construct TBL-blastoids and established senescence-related embryo models derived from oxidative stress-induced TBLCs. Results: Morphological and transcriptomic analyses revealed that TBL-blastoids exhibited characteristic blastocyst morphology, cell lineages, and a higher consistency in developmental rate. TBL-blastoids demonstrated the ability to develop into postimplantation structures in vitro and successfully implanted into mouse uteri, inducing decidualization and forming embryonic tissues. Importantly, senescence impaired the implantation potential of TBL-blastoids, effectively mimicking the impaired implantation ability and reduced pregnancy rates associated with advanced age. Furthermore, analysis of differentially expressed genes (DEGs) in human homologous deciduae revealed enrichment in multiple fertility-related diseases and other complications of pregnancy. The genes implicated in these diseases and the common DEGs identified in the lineage-like cells of the two types of TBL-blastoids and deciduae may represent potential targets for addressing impaired implantation potential. Conclusion: These results unveiled that TBL blastoids are an improved model for investigating implantation and early postimplantation, offering valuable insights into pregnancy-related disorders in women with advanced age and potential targets for therapeutic interventions.